2010
DOI: 10.2298/abs1003807v
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the genetic diversity in the wild boar population from the Podunavlje-Podravlje hunting area

Abstract: nem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Also, following the habitat destruction and decline in food availability due to human influence, their numbers have dwindled (Apollonio et al, 2010 (Alexander et al, 1996)) showed a high level of genetic diversity within the analyzed population. This report provides a starting point in genetic characterization of wild boar population in the western part of the Balkans and an important step towards the development of conservation and management plan for this species in the Balkan region (Veličković et al, 2010). Similar results were obtained in the wild boar population from Vojvodina, where the before mentioned five loci were also included (Djan et al, 2012).…”
Section: Introductionsupporting
confidence: 66%
“…Also, following the habitat destruction and decline in food availability due to human influence, their numbers have dwindled (Apollonio et al, 2010 (Alexander et al, 1996)) showed a high level of genetic diversity within the analyzed population. This report provides a starting point in genetic characterization of wild boar population in the western part of the Balkans and an important step towards the development of conservation and management plan for this species in the Balkan region (Veličković et al, 2010). Similar results were obtained in the wild boar population from Vojvodina, where the before mentioned five loci were also included (Djan et al, 2012).…”
Section: Introductionsupporting
confidence: 66%
“…The genetic diversity of wild boar populations from the other parts of the Balkans was inferred from microsatellite analyses. In wild boar populations from Bulgaria high level of genetic diversity and different genetic clusters were found (NIKOLOV et al, 2009), and same was proved for several wild boar populations from Serbia, Croatia and Bosnia (VELIČKOVIĆ et al, 2010(VELIČKOVIĆ et al, , 2012.…”
Section: Introductionsupporting
confidence: 64%
“…The genetic diversity and population structure of wild boar in the northern Dinaric Balkan region (the former Yugoslavia) is not well known because no extensive survey has been undertaken. The first characterizations of wild boar in the western part of the Balkans involved microsatellite analysis of several wild boar populations from Serbia, Croatia and Bosnia, and revealed high genetic diversity and population structuring (Veli ckovi c et al, 2010(Veli ckovi c et al, , 2012. These studies revealed structuring similar to that found in wild boar populations in Portugal (Ferreira et al, 2006(Ferreira et al, , 2009)in both areas the defined genetic clusters presented overlapping distributions and admixture in the contact areasand suggested that river barriers could not completely explain the observed divergence.…”
Section: Introductionmentioning
confidence: 97%
“…The first characterizations of wild boar in the western part of the Balkans involved microsatellite analysis of several wild boar populations from Serbia, Croatia and Bosnia, and revealed high genetic diversity and population structuring (Veli ckovi c et al, 2010(Veli ckovi c et al, , 2012. The first characterizations of wild boar in the western part of the Balkans involved microsatellite analysis of several wild boar populations from Serbia, Croatia and Bosnia, and revealed high genetic diversity and population structuring (Veli ckovi c et al, 2010(Veli ckovi c et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%